The Gini Trade Index: What can we learn from a new trade indicator? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2024)
This Policy Brief introduces the Gini Trade Index (GTI) as a new trade synthetic key performance indicator capable of capturing the different distribution of trade values across firm characteristics and across countries. The new indicator replicates the well-known features of the traditional Gini Index, a widely used metric for the skewness of several socioeconomic indicators, in particular income inequality. The Policy Brief calculates the Gini Trade Index for all EU member states and contrasts the case of Slovakia and Cyprus, the EU countries situated at the opposite ends of the Gini Trade Index. The paper finds that the GTI has increased over time in most EU countries and offers a tentative range of optimal GTI values. The final section offers several examples of trade policy initiatives that can reduce trade concentration and lead to greater participation of small and medium enterprises in global trade.
Keywords: 330; Foreign trade; Economic indicator; Index; Gini coefficient; Development indicator; Comparison; EU countries; Außenhandel; Wirtschaftsindikator; Index; Gini-Koeffizient; Entwicklungsindikator; Vergleich; EU-Staaten